Cloning, Structural Characterization, and Phylogenetic Analysis of Flower MADS-Box Genes from Crocus (Crocus sativus L.) - Athanasios S. Tsaftaris; Alexios N. Polidoros; Konstantinos Pasentsis; Apostolos Kalivas (The Scientific World Journal)
Crocus (Crocus sativus L.) is a crop species cultivated for its flowers and, more specifically, for its red stigmas. The flower of crocus is bisexual and sterile, since crocus is a triploid species. Its perianth consists of six petaloid tepals: three tepals in whorl 1 (outer tepals) and three tepals in whorl 2 (inner tepals). The androecium consists of three distinct stamens and the gynoecium consists of a single compound pistil with three carpels, a single three-branched style, and an inferior ovary. The dry form of the stigmas constitutes the commercial saffron used as a food additive, in the coloring industry, and in medicine. In order to uncover and understand the molecular mechanisms controlling flower development in cultivated crocus and its relative wild progenitor species, and characterize a number of crocus flower mutants, we have cloned and characterized different, full-length, cDNA sequences encoding MADS-box transcription factor proteins involved in flower formation.